Sandwiched ultra-thin yttria-stabilized zirconia layer to effectively and reliably block reduction of thin-film gadolinia-doped ceria electrolyte - Noh, Ho-Sung; Hong, Jongsup; Kim, Hyoungchul; Yoon, Kyung Joong; Lee, Jong-Ho; Kim, Byung-Kook; Son, Ji-Won (CERAMIC SOC JAPAN-NIPPON SERAMIKKUSU KYOKAI, 2015)
To investigate the possibility of reducing the thickness of the yttria-stabilized zirconia (YSZ) blocking layer of the gadolinia-doped ceria (GDC) electrolyte of the thin-film solid oxide fuel cell (TF-SOFC), a sandwich electrolyte configuration consisting of GDC/YSZ/GDC tri-layers is constructed. With only a 100 nm-thick YSZ layer, the TF-SOFC yielded high open circuit voltage (OCV) values (1.05Vat 650 degrees C), which indicates that the ultra-thin YSZ layer is deposited without massive defects and functions properly as a reduction blocking layer of the GDC electrolyte. The peak power density reaches approximately 2.1Wcm(-2) at 650 degrees C, which is at the ultimate performance level of the TF-SOFC. In electrochemical impedance spectra (EIS) analyses, an exaggerated low-frequency (LF) impedance at OCV is observed, which is considered to be originated from the chemical capacitance of the bottom GDC layer acting as an anode. In some cases, certain defects at the bottom GDC layer are identified, which are postulated to be caused by the chemical expansion and mechanical frailty of GDC exposed to the reducing atmosphere. Therefore, both the advantage and the disadvantage should be considered for reliably employing the sandwich electrolyte configuration. (C) 2015 The Ceramic Society of Japan. All rights reserved.
Keywords: OXIDE FUEL-CELLS; TEMPERATURE; ANODE; PERFORMANCE; COMPOSITE